Antibacterial Potential of Actinomycetes Isolates from Imperata (Imperata cylindrica L.) Rhizosfer Against Eschericia coli and Staphylococcus aureus - Feskaharny Alamsjah; Apriliana Wahyuni; Kawther Ameen Muhammed Saeed Aledresi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
Research on the Antibacterial Potential of Actinomycetes Isolates from the Rhizosphere of imperata (Imperata cylindrica L.) Against Eschericia coli and Staphylococcus aureus has been conducted at the Biota Laboratory of Sumatera, Andalas University from July to September 2020. This study aims to obtain actinomycetes isolates from plant rhizosphere reeds (Imperata cylindrica L.) which has the potential as an antibacterial against Escherichia coli and Staphylococcus aureus. This study used a survey method. The results showed that 4 isolated actinomycetes were found, all of which have antibacterial potential, which could inhibit the growth of Escherichia coli and Staphylococcus aureus.